The Effect of Product Quality and Brand Image on Customer Satisfaction and Customer Loyalty: - - Novia Nur Anisa; Andri Kusmayadi (International Journal of Economics (IJEC), 2025)
Brand image an important role in the marketing strategy that can be implemented by the originote company by providing the best facilities for its users to be able to provide trust, satisfaction so that consumers make continuous purchases of the product. The purpose of this study was conducted to determine the greatest influence on customer loyalty. This type of research is quantitative with a purposive sampling technique distributed through questionnaires to 100 male and female respondents who use originote products aged 18-45 years who have made at least 2 purchases in the last 3 months and domiciled in West Jakarta. Primary data analysis was carried out using the Structural Equation Modeling (SEM) method. The results of this study indicate that the 5 proposed hypotheses are accepted, and the product quality variable has the greatest direct influence on customer satisfaction. This study contributes to the originote company in maintaining and increasing customer loyalty by looking at several factors formed from each consumer complaint optimally and measurably. For further research, the researcher suggests expanding the research area and looking for objects in other fields